P Pembelajaran Matematika Realistik Terkait Peluang Berkonteks Permainan Ular Tangga - Aisy, Fadia Rohadatul; Fitriyani, Dila Eka; Ningrum, Rizqi Riskiyawani; Zuliana, Eka (JURNAL MathEdu (Mathematic Education Journal), 2024)
This research aims to determine the role of the snakes and ladders game which can help students discover the concept of opportunity using a Realistic Mathematics Learning approach. The method used in this research is the design research method. The research designed opportunity material using the PMRI approach for class VI MI NU Tholibin totaling 23 students with the snakes and ladders game as the beginning of learning. This research consists of three stages, namely (1) preliminary design or creating a Learning Trajectory Hypothesis (HLT) which contains a series of learning processes in 3 activities. (2) experiment (experiment). (3) review analysis. Based on this research, it was found that through the PMRI approach, students can determine the idea of ​​sample space, sample points, and the probability of an event by throwing a dice. With the learning direction (HLT) which starts with throwing the dice, determining the sample space, sample points and the probability of an event can help students understand probability material. Keywords : PMRI, Opportunity, Snakes and Ladders Game, Design Research.